The Intersection of Gender, Race, and Arrest in the Era of Cannabis Legalization - Meize, Mikala R. (Crime & delinquency, 2024)
The War on Drugs resulted in increased arrest rates for women. Most of these arrests have been for low-level offenses, often involving cannabis. As states legalize cannabis, it is important to examine trends in arrests for women in a setting of early cannabis law reform. We examine National Incident-Based Reporting System (NIBRS) monthly cannabis arrest rates in Colorado, one of the first two states to legalize cannabis for recreational purposes, from January 2010 through December 2016 using an interrupted time series approach. The interruption is conceptualized as the legalization of recreational marijuana in December 2012. Our results document an immediate statistically significant and sizable drop in cannabis-related arrests for women following legalization. However, troublesome racial and ethnic disparities persist.